2021
DOI: 10.2147/dmso.s309029
|View full text |Cite
|
Sign up to set email alerts
|

Diet Sugar-Free Carbonated Soda Beverage, Non-Caloric Flavors Consumption, and Diabetic Retinopathy: Any Linkage

Abstract: Purpose: Assessing diabetic retinopathy (DR) risk factors and daily nutrition habits are vital for prevention. This study aims to evaluate the relationship between diet soda cans, nonnutritive sweetener consumption, and diabetic retinopathy. Patients and Methods: A cross-sectional study was conducted among 200 patients attending a diabetes center in Tabuk City, Saudi Arabia, from September 2019 to July 2020. A structured questionnaire was used to collect patients' demographic factors, and DR risk factors inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 27 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…Of the latter, 57 were removed by exclusion criteria. Therefore, 21 papers were included in the systematic review; these comprised 14 cohort studies [19][20][21][22][23][24][25][26][27][28][29][30][31], five cross-sectional studies [32][33][34][35][36], a crossover study [37], a case-control study [38], and a randomized controlled trial [39].…”
Section: Resultsmentioning
confidence: 99%
“…Of the latter, 57 were removed by exclusion criteria. Therefore, 21 papers were included in the systematic review; these comprised 14 cohort studies [19][20][21][22][23][24][25][26][27][28][29][30][31], five cross-sectional studies [32][33][34][35][36], a crossover study [37], a case-control study [38], and a randomized controlled trial [39].…”
Section: Resultsmentioning
confidence: 99%
“…Mirghani and colleagues, using a cross-sectional study design, found that diet soda (sugar-free carbonated beverage) consumption was associated with a higher risk of DR ( p = 0.043) [ 22 ]. Another cross-sectional study by Fenwick and associates also found a positive association of diet drink (>4 cans [1.5 L]/week) consumption with proliferative DR (OR: 2.62, 95%CI: 1.14–6.06, p = 0.024) [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another proposed theory is that the overconsumption of other food or beverages might occur due to subjects overestimating the calories saved by substituting diet beverages for sugar-sweetened drinks [ 23 ]. However, further longitudinal studies are required due to a small sample size of 200 participants [ 22 ], as well as a lack of an account of changes in diet drink, i.e. from regular soft drink to diet soft drink for lifestyle modification upon diagnosis of diabetes, which could overestimate the relationship between diet soda and DR in the study [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations